2007
DOI: 10.1002/chem.200601708
|View full text |Cite
|
Sign up to set email alerts
|

Allyl ansa‐Lanthanidocenes: Single‐Component, Single‐Site Catalysts for Controlled Syndiospecific Styrene and Styrene–Ethylene (Co)Polymerization

Abstract: A series of new neutral allyl Group 3 metal complexes bearing ansa-bridged fluorenyl/cyclopentadienyl ligands [[Flu-EMe(2)-(3-R-Cp)]Ln(eta(3)-C(3)H(5))(THF)] (E=C, R=H, Ln=Y (2), La (3), Nd (4), Sm (5); R=tBu, Ln=Y (8), Nd (9); E=Si, R=H, Ln=Y (12), Nd (13)) were synthesized in good yields via salt metathesis protocols. The complexes were characterized by elemental analysis, NMR spectroscopy for diamagnetic complexes, and single-crystal X-ray diffraction studies for 2, 4, 9 and 12. Some of the allyl ansa-lanth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
59
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 118 publications
(39 reference statements)
12
59
0
Order By: Relevance
“…As for the ansa derivative 11 Nd , it was synthesized by ionic metathesis between K[1,3-(SiMe3)2C3H3] and [{Me 2 C(Cp)(Flu)}Nd(µ-Cl)] 2 and was found unsolvated. It was shown that 11 Nd acts as a single-component catalyst for the polymerization of styrene, and produces sPS albeit at a much lower rate (TOF = 20-60 h −1 ) than the regular allyl compounds {Me 2 C(Cp)(Flu)}RE(η 3 -C 3 H 5 )(THF) (RE = Y, La, Nd, 1000-17,000 h −1 ) [40]. Using DFT (Density Functional Theory) studies, the origin of the syndiospecificity control, due to a chain-end control mechanism (CEM), was proposed to result from the conjunction of the minimization of two repulsion effects: the classical phenyl (incoming monomer)-phenyl (last unit inserted) one during the growing of the polymer chain, and also of the repulsion between the fluorenyl ligand and the incoming styrene unit [41].…”
Section: Allyl Complexes For the Polymerization Of Styrenementioning
confidence: 99%
“…As for the ansa derivative 11 Nd , it was synthesized by ionic metathesis between K[1,3-(SiMe3)2C3H3] and [{Me 2 C(Cp)(Flu)}Nd(µ-Cl)] 2 and was found unsolvated. It was shown that 11 Nd acts as a single-component catalyst for the polymerization of styrene, and produces sPS albeit at a much lower rate (TOF = 20-60 h −1 ) than the regular allyl compounds {Me 2 C(Cp)(Flu)}RE(η 3 -C 3 H 5 )(THF) (RE = Y, La, Nd, 1000-17,000 h −1 ) [40]. Using DFT (Density Functional Theory) studies, the origin of the syndiospecificity control, due to a chain-end control mechanism (CEM), was proposed to result from the conjunction of the minimization of two repulsion effects: the classical phenyl (incoming monomer)-phenyl (last unit inserted) one during the growing of the polymer chain, and also of the repulsion between the fluorenyl ligand and the incoming styrene unit [41].…”
Section: Allyl Complexes For the Polymerization Of Styrenementioning
confidence: 99%
“…Hou and co-workers 18 have reported that rare-earth metal-based catalyst systems promote not only the syndiotactic homopolymerization of styrene, but also copolymerization with ethylene, in which the Cp¢Sc(CH 2 SiTMS) 2 /Ph 3 CÁB(C 6 F 5 ) 4 [Cp¢¼C 5 Me 4 (CH 2 TMS)] catalyst system produces a multi-block copolymer consisting of a crystalline SPS part and an ethylene-rich part. Carpentier and co-workers 19 have also reported an ansa-lanthanidocene catalyst that can synthesize a copolymer containing long syndiotactic styrene-styrene sequences separated by a single or a few ethylene units. Meanwhile, it has been previously reported that the copolymeric fraction separated from the mixture obtained by the CpTiCl 3 /MAO system contains a similar long syndiotactic styrene-styrene sequence.…”
Section: Introductionmentioning
confidence: 99%
“…The copolymers composition could be easily controlled by the monomer feeds over a wide range of composition, playing either with ethylene pressure and/or styrene concentration. The unusual higher affinity of those complexes towards styrene compared to ethylene was illustrated by the fact that no polymerization activity was detected at low styrene concentration (<1.2 mol/L) [95].…”
Section: Ansa-lanthanidocene Catalystsmentioning
confidence: 99%
“…The effect of bulky substituents on the Cp moiety as well as the influence of the bridge atom were also investigated and revealed that this system is very sensitive to an increase in the steric bulkiness and that a non-hindered environment is crucial to achieve good catalytic performances [95].…”
Section: Ansa-lanthanidocene Catalystsmentioning
confidence: 99%
See 1 more Smart Citation